Exploring the impacts of COVID-19 on Rohingya adolescents in Cox's Bazar: A mixed-methods study - Silvia Guglielmi; Jennifer Seager; Khadija Mitu; Sarah Baird; Nicola Jones (Elsevier, 2020)
This article explores how intersecting vulnerabilities faced by Rohingya adolescents living in Cox's Bazar, Bangladesh, have been exacerbated during the COVID-19 pandemic. Both the direct health impacts and the indirect repercussions of COVID-19 mitigation strategies have served to heighten pre-existing risks, preventing adolescents from reaching their full capabilities. This article provides empirical mixed-methods data from the Gender and Adolescence: Global Evidence (GAGE) longitudinal study, drawing on phone surveys adolescents aged 10-14 and 15-19 (1,761), qualitative interviews with adolescents aged 15-19 years (30), and key informant interviews (7) conducted between March and August 2020 with both Rohingya and Bangladeshi adolescents residing in refugee camps and host communities, respectively. While this article focuses on displaced Rohingya adolescents' experiences during COVID-19, we contextualize our findings by drawing on data collected from Bangladeshi adolescents who serve as comparators. Findings highlight that the pandemic has lead to a decline in Rohingya adolescents' reported health status, exacerbated food insecurity, educational and economic marginalization and bodily integrity risks, amongst both girls and boys. This paper concludes by reflecting on the policy implications necessary to safeguard refugee adolescent trajectories in the context of COVID-19.